Increasing community food security through aquaponic and aeroponic cultivation - Arsad Bahri; Jabal Rahmat Ashar; Zakia Asrifah Ramly; Andi Wahyudi Fajriansyah Al-Ghifari; Nur Aisyah Ainun; Yusuf Arisandi; Wahyu Hidayat (Universitas Muhammadiyah Malang, 2022)
The topographical conditions in Bulo-Bulo Village, Jeneponto Regency, South Sulawesi, tend to be bumpy and rocky, which is the main problem in farming. Locals exclusively use growing methods because there is little public awareness about cultivation technologies. The community employs a number of different fish farming systems. Additionally, the cost of fish feed has a tendency to change, making it harder for people to satisfy their needs for the primary protein source. The community can be counseled on land use by using aquaponic and aeroponic systems as a possible solution to the issue. Regardless of climatic conditions or current land characteristics, aquaponic technology is recognized as a substitute for integrated farming systems. By providing counseling, instruction, and hands-on support to the residents of Bulo-Bulo Village, the strategy is put into action. The results of this action take the shape of autonomous aquaponic and aeroponic installations that grow food crops and fish in the same space to reduce production costs and increase earnings. Every family in the community is intended to be able to benefit from this activity and use the farming technology in order to reinforce and encourage long-term improvements in the nation of Indonesia's food security.